Photocatalytic Properties of Micro-Crystalline Polyoxometalate Synthesized Using Microemulsion Method - Nepolean Raj, A. Arokia; Jeyabalan, T. (Asian Journal of Chemistry, 2017)
In present study, a photocatalytic degradation of rhodamine-B by micro-crystalline polyoxometalates (POM) is investigated. The polyoxometalates catalyst is synthesized using microemulsion method and characterized by FT-IR, XRD and SEM. Photocatalytic degradation experiment is carried out in a setup by UV light irradiation in presence of catalyst and the degradation progress is evaluated using UV-visible spectrophotometer.